Peran Pendidik dalam Membangun Empati Anak Melalui Metode Role Playing di Kelompok Bermain Aisyiyah 01 Kota Semarang - Maharani Lulu Chairunnisa; Tri Joko Raharjo (Lembaga Pengembangan Kinerja Dosen, 2024)
Preschool educational institutions from the lowest to the highest level must act as agents of developing children's empathy that should be emulated by other educational institutions, by having empathy children will understand that not all their desires through others can be fulfilled. With empathy children will be able to build relationships and be accepted by others. This study aims to describe the role of educators in building children's empathy through the role playing method in the Aisyiyah 01 playgroup in Semarang City and related to the internal and external challenges faced by educators in building children's empathy. This study uses a qualitative descriptive research method. The implementation technique is to collect data through observation, interviews and documentation. Data analysis uses an interactive model of data collection, data reduction, data presentation and drawing conclusions. The results of the study were obtained through the role of educators and strategies carried out in carrying out the role playing method to build children's empathy where educators play an important role in teaching and also provide supporting factors in the role playing method. Internal factors include the lack of available time allocation and also the support of teaching aids in developing the method, while external factors are that the learning curriculum is less flexible